Different mechanisms of adjustment to a change of the photoperiod in the suprachiasmatic and liver circadian clocks - Sosniyenko, Serhiy; Parkanová, Daniela; Illnerová, Helena; Sládek, Martin; Sumová, Alena (American journal of physiology. Regulatory, integrative and comparative physiology, 2010)
Changes in photoperiod modulate the circadian system, affecting the function of the central clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus. The aim of the present study was to elucidate the dynamics of adjustment to a change of a long photoperiod with 18 h of light to a short photoperiod with 6 h of light of clock gene expression rhythms in the mouse SCN and in the peripheral clock in the liver, as well as of the locomotor activity rhythm. Three, five, and thirteen days after the photoperiod change, daily profiles of Per1, Per2, and Rev-erbalpha expression in the rostral, middle, and caudal parts of the SCN and of Per2 and Rev-erbalpha in the liver were determined by in situ hybridization and real-time RT-PCR, respectively. The clock gene expression rhythms in the different SCN regions, desynchronized under the long photoperiod, attained synchrony gradually following the transition from long to short days, mostly via advancing the expression decline. The photoperiodic modulation of the SCN was due not only to the degree of synchrony among the SCN regions but also to different waveforms of the rhythms in the individual SCN parts. The locomotor activity rhythm adjusted gradually to short days by advancing the activity onset, and the liver rhythms adjusted by advancing the Rev-erbalpha expression rise and Per2 decline. These data indicate different mechanisms of adjustment to a change of the photoperiod in the central SCN clock and the peripheral liver clock.
Keywords: Reverse Transcriptase Polymerase Chain Reaction; Photoperiod; nucleus suprachiasmaticus; komplementární DNA; Period Circadian Proteins; myši; cirkadiánní proteiny Period; Light; Nuclear Receptor Subfamily 1, Group D, Member 1; transkripční faktory ARNTL; zvířata; fotoperioda; sociální přizpůsobení; Darkness; Liver; Suprachiasmatic Nucleus; světlo; Organ Specificity; Animals; Biological Clocks; Motor Activity; Mice; Social Adjustment; regulace genové exprese; polymerázová řetězová reakce s reverzní transkripcí; orgánová specificita; biologické hodiny; Gene Expression Regulation; DNA, Complementary; jaderné receptory - podrodina 1, skupina D, člen 1; játra; Circadian Rhythm; tma; pohybová aktivita; ARNTL Transcription Factors; cirkadiánní rytmus